The Escherichia coli heat shock gene htpY: mutational analysis, cloning, sequencing, and transcriptional regulation. - Missiakas, D (1993)
We have identified a new heat shock gene, designated htpY, located 700 bp upstream of the dnaK dnaJ operon. We cloned it and showed that it is transcribed clockwise vis-à-vis the Escherichia coli genetic map, in the same direction as the dnaK dnaJ operon. The htpY gene encodes a 21,193-Da polypeptide. Promoter mapping experiments and Northern (RNA) analysis showed that the htpY gene belongs to the classical heat shock gene family, because the transcription from its major promoter is under the positive control of the rpoH gene product (sigma 32) and resembles canonical E sigma 32-transcribed consensus promoter sequences. This conclusion has been strengthened by the construction and analysis of a phtpY-lacZ promoter fusion. Despite the fact that htpY null bacteria are viable, the expression of various E sigma 32 heat shock promoters is significantly decreased, suggesting that HtpY plays an important role in the regulation of the heat shock response. Consistent with this interpretation, overproduction of the HtpY protein results in a generalized increase of the heat shock response in E. coli.